1995
DOI: 10.1016/0014-2999(95)00428-n
|View full text |Cite
|
Sign up to set email alerts
|

Role of dopamine D1 and D2 receptors in the nucleus accumbens in jaw movements of rats: a critical role of the shell

Abstract: Given the differences in the dopamine neurotransmission between the shell and the core of the nucleus accumbens, as well as the differential involvement of these two domains in oral behaviour of rats, it was decided to determine whether or not dopamine Dj and/or dopamine D 2 receptors differentially direct oral behaviour in these two domains in rats. Intra-accumbens injections of the dopamine D, receptor agonist ( + )-6-chloro-7,S-dihydroxy-3-alIyl-1 -phenyl-2,3,4,5-letrahydro-l/7-3-benzazepine (SKF 82958: 5 j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…The present results are consistent with findings that MAM-E15 exposed offspring show higher susceptibility for chronic haloperidol-induced orofacial dyskinesias (Johansson 1990). Given that the striatal retogions innervated by the frontal cortex (i.e., medial and ventral striatum) mediate oral dyskinesias (Cools et al 1995;Hamid et al 1998;Prinssen et al 1996), the more potent effect of PCP on oral movements in the MAM-E17 animals is consistent with a hypo-function of the glutamatergic frontal corticostriatal pathway (Tamminga 1998). …”
Section: Dysfunction Of the Frontal Corticostriatal Circuitssupporting
confidence: 91%
“…The present results are consistent with findings that MAM-E15 exposed offspring show higher susceptibility for chronic haloperidol-induced orofacial dyskinesias (Johansson 1990). Given that the striatal retogions innervated by the frontal cortex (i.e., medial and ventral striatum) mediate oral dyskinesias (Cools et al 1995;Hamid et al 1998;Prinssen et al 1996), the more potent effect of PCP on oral movements in the MAM-E17 animals is consistent with a hypo-function of the glutamatergic frontal corticostriatal pathway (Tamminga 1998). …”
Section: Dysfunction Of the Frontal Corticostriatal Circuitssupporting
confidence: 91%
“…As mentioned above, the ventrolateral striatum has been identified as a region particularly important in the production of oral movements (Delfs and Kelley, 1990;Kelley et al, 1988;ScheelKruger and Arnt, 1985). The novel finding of a similar magnitude of decreased labeling in the accumbens is also of relevance, as studies have shown enhanced oral movements after pharmacological stimulation of the nucleus accumbens (Koene et al, 1993;Cools et al, 1995). Interestingly, examination of accumbal tissue from individuals treated for years with neuroleptics showed a decrease in ChAT activity (Bird et al, 1977).…”
Section: Discussionmentioning
confidence: 90%
“…In the ACB, synergistic effects of D 1 and D 2 agonists have been reported for locomotor activity (Dreher and Jackson, 1989;Essman et al, 1993;Koshikawa et al, 1996a), jaw movements (Cools et al, 1995;Koshikawa et al, 1996b), and neuronal firing (White, 1987). However, there is no clear information whether the interaction of D 1 and D 2 receptors within the ACB can produce a cooperative or synergistic effect on reinforcement processes.…”
Section: Abstract: Dopamine D 1 Receptor; Dopamine D 2 Receptor; Skfmentioning
confidence: 99%